Using Bagasse and Aluminum Sulfate-Modified Bagasse as Adsorbents for Treatment of Industrial Cutting Fluid Wastewater in Laboratory and Pilot Scales - Natthaporn Pongtaveekan; Piyapan Thammajaree; Kowit Piyamongkala; Nattaya Pongstabodee; Von Louie R. Manguiam (Journal of Engineering)
Industrial cutting fluid wastewater (CFW) is considered as hazardous substance due to its detrimental effects to the environment and workers welfare. Treatment of this type of wastewater was sometimes disregarded due to lack of knowledge and resources. However, adsorption, a straightforward approach, was used in this study to address this problem. The feasibility of the bagasse and modified bagasse in the adsorption of CFW was determined. Varying the adsorbent dosage resulted in an increase in the percent adsorption, whereas a decline for the adsorption capacity at equilibrium using a single-stage batch laboratory- and pilot-scale adsorption. The point of zero charge of the bagasse and the modified bagasse was measured to be at pH 5.5 and 2.4, respectively. The experiment also determined that, for a liter of CFW, 10.2 g and 59.2 g of the modified bagasse are required under laboratory- and pilot-scale systems, respectively. Isotherms of Langmuir, Freundlich, and Temkin were used in order to describe the adsorption process. It was determined that the surface heterogeneity and the pore size contributed to the adsorption of CFW; thus, Freundlich isotherm best fitted the data. Functional groups were verified using FTIR analysis and the heat of combustion, and their proximate analyses were determined. Based on the results under laboratory- and pilot-scale systems, modified bagasse is a viable material for the adsorption of CFW and solid fuel source.